2022
DOI: 10.1007/s11606-022-07635-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of Women Leaders with Women Program Director and Trainee Representation Across US Academic Internal Medicine

Abstract: Background Women are underrepresented within internal medicine (IM). Whether women leaders attract women trainees is not well explored. Objective To characterize leader and trainee gender across US academic IM and to investigate the association of leader gender with trainee gender. Design Cross-sectional study. Participants Leaders (chairs, chiefs, program directors (PDs)) in 2018 and trainees (residents, fellows) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…directorship positions provide more mentorship opportunities to female trainees and could lead better recruitment of female residents and fellows into respective programs. A recent study of internal medicine programs, however, did not find this to be the case with no association found between presence of a female program director and number women trainees (15); this has of yet to be investigated in pediatric urology, however. It has been suggested that an apparent discrepancy between representation of women in program directorship positions compared to department/division chief positions is a result of women generally being guided toward more clinic-educator career tracks rather than traditional researchbased tracks that have a higher likelihood of major departmental leadership advancement and thus promotion (16).…”
Section: B C Amentioning
confidence: 90%
“…directorship positions provide more mentorship opportunities to female trainees and could lead better recruitment of female residents and fellows into respective programs. A recent study of internal medicine programs, however, did not find this to be the case with no association found between presence of a female program director and number women trainees (15); this has of yet to be investigated in pediatric urology, however. It has been suggested that an apparent discrepancy between representation of women in program directorship positions compared to department/division chief positions is a result of women generally being guided toward more clinic-educator career tracks rather than traditional researchbased tracks that have a higher likelihood of major departmental leadership advancement and thus promotion (16).…”
Section: B C Amentioning
confidence: 90%